ANALISIS STRATEGI PENINGKATAN KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI SUMATERA UTARA - Dinda Ratulangi; Juniyanti Siagian; Putri Alisia Silaen; Wildan Arifin Batu Bara; Fikri Dwi Septian; Farhan Ramadhan; Zannah Zania Zahra Matondang (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze strategies for improving the quality of population administration services at the Population and Civil Registration Office of North Sumatra Province. The research method used was a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Informants in this study consisted of employees and community users of population administration services. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the strategy for improving service quality was implemented through the implementation of service digitalization, improving human resource competency, and simplifying service procedures. Furthermore, efforts to improve facilities and infrastructure contributed to the effectiveness of public services. However, several obstacles remain, such as network limitations, a lack of public understanding of digital services, and a high volume of service requests. The conclusion of this study indicates that the implemented strategy has had a positive impact on improving the quality of population administration services, although several aspects still require optimization to achieve more effective, efficient, and responsive public services to community needs.